2016
DOI: 10.15226/jnhfs.2016.00156
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Hunger-Free Kids Act Increases Phytochemicals in Menus and Curriculum Furthers Identification of Phytochemical-Rich Foods

Abstract: Objective This study evaluated whether providing the Fruits and Vegetables (F/V) required by the Healthy Hunger-Free Kids Act (HHFKA) increased phytochemical/antioxidant content of school lunches. Additionally, the ability of adolescents to apply their nutritional knowledge following participation in a nutrition-focused science-based curriculum was assessed. Methods Changes in antioxidant/phytochemical content from F/V offered in school lunch menus were analyzed Pre-and Post-HHFKA. Food logs completed by 717… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Frequently, studies reported positive impacts of school feeding programs for child food security and nutrition. In the United States, subsidized school meal programs that featured healthier meal options for food insecure children succeeded in maintaining student participation (Vaudrin et al, 2018), and instituting standards for the nutritional quality of meals changed the types of foods selected by students (Schwartz et al, 2015;Brewer et al, 2016). In San Diego, US, strikingly high levels of food insecurity could have been addressed by government programs, but only through recognizing the challenges of underserved populations (Smith et al, 2017).…”
Section: Advancing Physical and Economic Access To Adequate Food Through Appropriate Actions By Governments And Non-state Actors (A)mentioning
confidence: 99%
“…Frequently, studies reported positive impacts of school feeding programs for child food security and nutrition. In the United States, subsidized school meal programs that featured healthier meal options for food insecure children succeeded in maintaining student participation (Vaudrin et al, 2018), and instituting standards for the nutritional quality of meals changed the types of foods selected by students (Schwartz et al, 2015;Brewer et al, 2016). In San Diego, US, strikingly high levels of food insecurity could have been addressed by government programs, but only through recognizing the challenges of underserved populations (Smith et al, 2017).…”
Section: Advancing Physical and Economic Access To Adequate Food Through Appropriate Actions By Governments And Non-state Actors (A)mentioning
confidence: 99%
“…The change in standards resulted in increased fruit and vegetable offerings provided at lunch and for the first time, both fruits and vegetables were served daily. Amid concerns that a revised and restrictive school meals menu might create unintended consequences such as greater food waste, school-based research studies have begun to demonstrate that the HHFKA's supportive built environment can enhance fruit and vegetable consumption [1].…”
Section: Introductionmentioning
confidence: 99%